Stretching tension effects in permeability transition pores of inner mitochondrial membrane - Khmelinskii, Igor (2021)
Presently a mechanism of permeability transition pore (PTP) opening was proposed and discussed. This mechanism is based on mechanical stretching of inner mitochondrial membrane (IMM) caused by mitochondrial swelling (MS). The latter is induced by osmotic pressure generated by solute imbalance between the matrix and the surrounding cyto(sarco)plasm. Modelled by the Monte-Carlo method, an IMM fragment of 350 simulated biological molecules exhibited formation of micro-domains containing two protein and seven phospholipid molecules. The energies (-0.191 eV per molecule) in these micro-domains were significantly larger than those (-0.375 eV per molecule) of other parts of the IMM fragment. Stretching forces applied to such domains expanded them much more than other parts of the IMM fragment. We identify these micro-domains as the PTPs. Both linear and nonlinear functions were used for the strain-stress relation of the IMM fragment, with nonlinear effects more important at large IMM stretching strains. Thus, two main factors are incorporated into the PTP opening mechanism: (1) presence of micro-domains in the IMM structure and (2) IMM stretching stress caused by MS. Taking into account both of these factors, the equation for the probability of PTP opening was deduced, with matrix Ca2+ and H+ ionic concentrations as its parameters. Note that the equation deduced was similar to an earlier reported empirical equation describing PTP opening dynamics. This correspondence provides support to the presently proposed mechanism. Thus, a new look at the PTP opening mechanism is provided, of interest to various research areas related to mitochondrial biophysics.